Improved RP‐HPLC method for determination of bovine lactoferrin and its proteolytic degradation in simulated gastrointestinal fluids. (8th June 2012) - Yao, Xudong; Bunt, Craig; Cornish, Jillian; Quek, Siew‐Young; Wen, Jingyuan
ABSTRACT The objective of this study was to qualitatively and quantitatively evaluate bovine lactoferrin (bLf) and its stability using a rapid RP‐HPLC method. bLf could be rapidly detected within 20 min and quantitated at levels down to 5 µg/mL, and the equation of linearity was y = 86.10x + 178.31 with the correlation coefficient (r2) 0.9997. Quantitative data obtained in the present study proved the improved RP‐HPLC method to be a sensitive and accurate analytical tool for bLf determination. The proteolytic cleavage of bLf in simulated human gastrointestinal fluids was further analyzed by RP‐HPLC, and found to follow pseudo‐first‐order kinetics. The typical equation obtained by pepsin was log10 [At]/[A0] = −0.03x (r2 = 0.85), and log10 [At]/[A0] = −0.01x (r2 = 0.81) for trypsin and chymotrypsin combination. Pepsinolysis of bLf in simulated gastric fluid was relatively fast with the half‐life t1/2 23.1 min. The digestion of bLf in simulated intestinal fluid was slower with about a 3‐fold increase in half‐life (69.3 min). After the complete proteolysis of bLf, small cleaved peptide fragments were fully separated and identified by RP‐HPLC. The proteolytic study indicated that this validated RP‐HPLC was able to evaluate bLf stability though monitoring the derivatization products. Copyright © 2012 John Wiley & Sons, Ltd.